Soccer-specific fatigue decreases reactive postural control with implications for ankle sprain injury - Greig, M.; McNaughton, L. (Research in Sports Medicine, 2014)
To quantify the influence of soccer-specific fatigue on reactive dynamic balance, ten male professional soccer players (age 24.7 ± 4.4 yr, body mass 77.1 ± 8.3 kg, VO2max 63.0 ± 4.8 ml·kg·min-1) completed an exercise protocol replicating the activity profile of match-play. Pre-exercise, and at 15 min intervals, players completed three balance tasks requiring response to a system perturbed to induce either plantar flexion of the ankle or inversion of the ankle (by rotation or translation). ANOVA revealed a significant main effect for exercise duration in each task, with both reaction time and total centre of gravity displacement tending to increase during each half. In all three trials there was a significant increase in medio-lateral and anterior-posterior displacement, the planar perturbation of the platform evoking a multi-angular response. Dynamic balance performance decreased as a function of time during each half, suggesting a greater risk of injuries at these specific times, in accord with epidemiological observations of ankle sprain injury.